Christian love in inter-religious perspectives - Kruger, Kobus (HTS teologiese studies, 2016)
The article approaches the phenomenon of love from a theoretical perspective in which the interconnectedness of religions is constitutive of every religion, including Christianity, in its relative singularity. It explores a historical context in which Christianity with its unique message of love does not stand alone among the religions of the world, and a theoretical context that could account for that historical context, without abandoning or diluting the Christian vision, but enriching it, adding depth to the notion ‘Christianity’ in its most essential sense. The argument is developed by first introducing seven religious perspectives on love. This is followed by metaphysical-mystical reflections in which the concept ‘Infinitude’ features. The argument proceeds concentrically outwards, starting from Christianity as centre, seen as one magnificent dewdrop reflecting an infinite net of interdependence.